Enhancing self-concept through short story reading analysis and reflective writing (2021)
This qualitative case study, conducted with a group of undergraduate students ascribed to the School of Public Accountancy in Externado de Colombia University, intended to motivate them to identify their own values and potentials to heighten self-concept through the analysis of short-story content and the creation of thoughtful writing worksheets. The initial stage of this study pondered the reflection on students’ self-awareness, which yielded the analysis of their behaviour when acknowledging their own virtues versus their tendency to highlight their disadvantages and inaccuracies and adopt pedagogical approaches to nurture consciousness of their positive qualities. In doing so, audio-recordings, students’ artefacts, a self-reflection questionnaire, and the teacher’s field notes allowed data collection to state the results of the current research. Findings show that short story content analysis and reflective writing had a positive impact on the students’ awareness of ill-treatment as a cause of disappointment; and reflective writing as a source of positive self-esteem. In the same way, students enhanced self-concept, as they valued personality strengths and admitted their weaknesses through reflective writing activities proposed in the worksheets developed by the teacher researcher. Finally, as this research advocates reflective short story writing worksheets that consider students’ personal and social values, attitudes, and selfperception, it confronts culture domination of standardised and decontextualized EFL materials that privilege global culture at the expense of experiential one.